Do Illicit Financial Flows Hurt Tax Revenues? Evidence from the Developing World - Combes, Jean-Louis (World Bank, Washington, DC, 2021)
Recent work draws attention to the fragility of domestic tax revenues—a vital resource for the developing world—to illicit financial flows. To cope with two major challenges in the illicit financial flows–tax revenues relationship—related to the mere illicit financial flows measurement and reverse causality—this paper exploits the Financial Action Task Force data using an impact assessment analysis. Estimations reveal a significant tax revenue loss in countries associated with important illicit financial flows with respect to comparable countries without important illicit financial flows. Moreover, this causal effect—estimated as being economically meaningful—is supported by a large robustness section, and in particular remains unchanged when using several “doubly robust” estimators. Lastly, it unveils heterogeneities in the impact of illicit financial flows on tax revenues, related to the type of tax—a significant loss for indirect but not for direct taxes—and the considered environment. Therefore, policies combating illicit financial flows—for example, by developing institutions or a sound financial system, as shown by the estimations—may provide additional tax revenues for the developing world.